Sejarah Perkembangan Tari Ronggeng Paser di Kabupaten Penajam Paser Utara - Zahra Zahra; Muhamad Sopyan; Jamil Jamil; Wingkolatin Wingkolatin; Sainal A.; Muhammad Azmi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the historical development of the Ronggeng Paser in Penajam Paser Utara (2017–2022) and the community’s efforts to preserve it. This research adopts a descriptive qualitative approach using historical methods. The study was conducted in Penajam Paser Utara. The findings reveal that the Ronggeng Paser has existed since the era of animism and dynamism, and its development in Penajam Paser Utara from 2017 to 2022 has shown positive progress. Preservation efforts for the Ronggeng Paser have been carried out through various means, including protection, development, and utilization of the dance in artistic performances and cultural festivals.